Facility Layout Improvement for Enhancing Productivity: An Application of Systematic Plant Layout (Vallis Aurea, 2019)
One of the major prerequisites for effective operations of a manufacturing plant depends on the sufficiency of a good facility layout. A well-planned facility layout enables better utilization of resources and thereby better production control. The purpose of this research was to analyse the effectiveness of the layout improvement through systematic plant layout planning (SLP) method. Factors like relationship diagram/affinity chart, material flow, space requirements etc. were studied to propose a modified layout according to the SLP method.The study found that the improved plant layout not only optimised the material flow and space requirements but in addition it enormously reduced the material handling cost of the plant thereby bringing better operational efficiency.